Теоретичні засади дослідження лінгвокультурних кодів - Пустовалова, Віра; Pustovalova, Vira (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розглянуто сучасні підходи до трактування поняття лінгвокультурного коду. Виявлено типологічні й функціональні характеристики лінгвокультурних кодових систем, описано способи їхньої класифікації та ієрархічного впорядкування. Для позначення в лінгвокультурології систем нижчого рівня використано термін «субкод».The paper deals with the theoretical aspects of the linguocultural codes study as semiotic phenomenon. The existing approaches to the interpretation of the term «linguocultural code» in comparison with the term «code» as the basic unit of semiotics are examined. The distinctive features of the linguocultural code are accented: the secondary meaning of the units, the archetype nature, the group nature of secondary meanings formation, the systematic usage. The typological and functional characteristics of the code systems are identified. The most popular way of classifying the linguocultural code units on the substantial (based on the unity of the expression plan) and conceptual (based on the unity of the meaning plan) characteristics is described. The basic thematical groups of units are pointed out. The hierarchical way of dividing the units of code into thematic groups is defined. To name these groups the term «subcode» is proposed
The Theoretical Background of the Linguocultural Codes Investigations
Keywords: лінгвокультурний код; субкод; семіосфера; вторинна номінація; субстанціональний код; концептуальний код; linguocultural code; subcode; semiosphere; secondary nomination; substantial code; conceptual code